Cardiac Rehabilitation in Coronary Artery Disease: Improving Outcomes and Adherence - Rahman, Md Toufiqur; Islam, AKM Monwarul; Majumder, AAS (Bangladesh Journal of Medicine, 2023)
Cardiac rehabilitation (CR) is a program that aims to improve the cardiovascular health of patients with coronary artery disease (CAD) through a multidisciplinary approach. CR typically includes exercise training, risk factor modification, psychosocial support, and education. Studies have shown that CR can improve exercise capacity, reduce angina symptoms, enhance overall quality of life, and reduce the risk of recurrent cardiovascular events. Despite the benefits of CR, adherence remains a challenge, and many patients with CAD do not participate in these programs. Strategies to improve adherence to CR include patient education, personalized goal setting, motivational interviewing, and peer support. Encouraging and supporting patients with CAD to participate in CR programs is crucial for the secondary prevention and long-term management of their condition. CR programs are typically supervised by healthcare professionals, such as cardiac rehabilitation specialists, exercise physiologists, and dietitians, who work together to develop personalized treatment plans for each patient. Exercise training is a key component of CR, and programs may involve aerobic and resistance training, as well as other forms of physical activity such as yoga or tai chi. Risk factor modification focuses on controlling blood pressure, reducing cholesterol levels, managing diabetes, and promoting smoking cessation. Psychosocial support and education may include counseling, stress management, and education on nutrition and medication management. While CR programs are effective, access to these programs may be limited for some patients, particularly those in underserved communities or rural areas. Tele-rehabilitation, which uses technology to provide remote delivery of CR services, has shown promise in increasing access to CR for patients who may not have access to traditional in-person programs. Overall, CR is a vital component of the management of CAD, and its benefits extend beyond cardiovascular health to include improvements in overall quality of life. It is important to raise awareness about the importance of CR and to work towards increasing access to these programs for all patients with CAD. J Medicine 2023; Vol. 34, No. 2(1) Supplement: 213